Pengukuran Anion Anorganik Secara Simultan dalam Sampel Air Tanah dan Air Ledeng Menggunakan Kromatografi Ion - Amin, Muhammad; Oktavia, Budhi (Departemen Kimia FMIPA UNP, 2023)
Ion chromatography is an advanced and highly sensitive form of ion exchange chromatography that can effectively detect ion species, whether organic or inorganic ions. This research study utilized ion chromatography with a suppressed conductivity detection system to separate and measure the concentration of fluoride, chloride, nitrite, bromide, nitrate, phosphate, and sulfate ions in groundwater and tap water samples. The eluent solution used in this separation contained 6.0 mmol/L Na2CO3 and 0.25 mmol/L NaHCO3, which was crucial in ensuring the accuracy and selectivity of the detections. The samples were collected in 3 sub-districts in Ternate City, and the study's findings shed light on the water quality in the area.